PENGARUH NORMA SUBYEKTIF,DAN TAM TERHADAP NIAT MENGGUNAKAN SISTEM ERP - Susilaputri, Rizki Endah (Fakultas Ekonomi dan Bisnis Islam, 2017)
ERP is a system used by the company to integrate all business processes. This study aimed to determine the effect of Subjective Norm and Technology Acceptance Model (TAM) of the Intention to Use ERP Systems. TAM in this study was measured by two indicators: Perception Perceived Usefulness and Ease of Use.Respondents in this study were users of ERP systems on PT. Semen Gresik (Persero), Tbk. Questionnaires were the primary data used in this research and random sampling was used as data collection method. Questionnaires were distributed about 70 copies but only 63 were returned, and 3 of them were incomplete questionnaires. The data analysis technique used was Partial Least Square, with the help of Smart PLS 2.0 software.The results of this study are: 1) Subjective Norms have positive significant effect on Intention to Use ERP Systems. 2) Perceived Usefulness have positive significant effect on Intention to Use ERP Systems. 3) Perceived Ease of Use have positive significant effect on Intention to Use ERP Systems.